Nitrogen and radiation effects during the active spike-growth phase on floret development and biomass partitioning in 2- and 6-rowed barley isolines - Arisnabarreta Dupuy, Sebastián (2010)
The paramount importance of accumulated biomass in active-growing spikes over the number of grains per unit area has been well documented. However, it is not clear how different nitrogen (N) and radiation supplies during the active spike-growth phase alter the dynamics of floret primordia initiation and survival to establish the number of fertile florets and grains in 2- and 6-rowed barley. The objective of this paper was to evaluate how biomass and N partitioned between vegetative and reproductive organs alter the development of potential grains (i.e. floret primordia), when 2- and 6-rowed barley is grown under different radiation and N levels during their active spike-growth phase. A field experiment was carried out using two near-isogenic lines differing in the spike type and grown under contrasting radiation and N levels around the active spike-growth phase. Floret primordia development and biomass and N partitioning towards vegetative and reproductive organs were analysed. The results showed significant genotype ×radiation ×N level interactions on the dynamics of generation and abortion of reproductive structures. Under non-limiting N conditions, reductions in radiation levels strongly reduced the number of differentiated florets, although the effects were higher in 6- than in 2-rowed barley types. The higher the N supply, the higher the floret development stage reached when the spikes started growing at their maximum growth rates, increasing floret survival in that way. A threshold of floral development could not be found at any time in the crop cycle that guaranteed a fertile floret stage at heading. As it was not possible to identify a direct effect of N on the establishment of fertile florets, the efforts for further rising yield potential in barley should be focused on processes influencing partitioning of assimilates to reproductive growth during the critical period.